2019
DOI: 10.3389/fnins.2019.00351
|View full text |Cite
|
Sign up to set email alerts
|

Robust Generation of Person-Specific, Synchronously Active Neuronal Networks Using Purely Isogenic Human iPSC-3D Neural Aggregate Cultures

Abstract: Reproducibly generating human induced pluripotent stem cell-based functional neuronal circuits, solely obtained from single individuals, poses particular challenges to achieve personalized and patient specific functional neuronal in vitro models. A hallmark of functional neuronal assemblies, synchronous neuronal activity, can be non-invasively studied by microelectrode array (MEA) technology, reliably capturing physiological and pathophysiological aspects of human brain function. In our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 54 publications
(95 reference statements)
6
78
0
1
Order By: Relevance
“…In the present study, we analyzed the functional and cellular impact of hCSF on hiPSC-3D neural aggregates (3D NAs) comprised of cortical neurons, glial cells, and residing proliferative neural cells ( Edri et al., 2015 , Izsak et al., 2019 ). For this purpose, we applied patch-clamp technique, microelectrode array (MEA) recordings, and confocal imaging on 3D NAs exposed to hCSF obtained from healthy adult individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we analyzed the functional and cellular impact of hCSF on hiPSC-3D neural aggregates (3D NAs) comprised of cortical neurons, glial cells, and residing proliferative neural cells ( Edri et al., 2015 , Izsak et al., 2019 ). For this purpose, we applied patch-clamp technique, microelectrode array (MEA) recordings, and confocal imaging on 3D NAs exposed to hCSF obtained from healthy adult individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, five BD-iPSC lines and four control-iPSC lines were used for the generation of NSCs and mature 3D neural aggregates comprising of neurons, astrocytes, and oligodendroglia cells 12 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A copy of the detailed method description from Vizlin-Hodzic et al 8 can be found in the supplementary information. In the present study, five BD-iPSC lines and four control-iPSC lines were used for the generation of NSCs and mature 3D neural aggregates comprising of neurons, astrocytes, and oligodendroglia cells 12 (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations